“A Very Garden of the Lord”? Hired Hands, Farm Women, and Sex Crime Prosecutions on the Prairies, 1914-1929 - Erickson, Lesley (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2001)
AbstractIn the brief fifteen-year period between the outbreak of World War I and the onset of the Depression a significant number of agricultural labourers stood accused in western Canadian criminal courts for raping, indecently assaulting, or seducing farm women or their daughters. These “hired hand” cases provide an opportunity to explore how considerations of class, ethnicity, and gender shaped both the nature of sexual conflict and violence during the settlement period and the meanings that western Canadians attached to it. Cases of gender and class conflict between farm hands and farm women belied Utopian visions of the West that depicted the region as a land that was free of the class and gender restraints that typified the Old World. Sex crime prosecutions served as a means for the criminal courts and farm families to identify and punish men and women, who, for complex reasons, did not share the values or live up to the ideals of the emerging capitalistic society.